The increasing big gap of carbon sink between the western and eastern Pacific in the last three decades - Zhong, Guorong; Li, Xuegang; Song, Jinming; Qu, Baoxiao; Wang, Fan; Wang, Yanjun; Zhang, Bin; Tian, Detong; Ma, Jun; Yuan, Huamao; Duan, Liqin; Li, Ning; et al. (Frontiers in Marine Science, 2022)
The Pacific Ocean is one of the important carbon sink regions, and there is a significant west-east difference in sea-air CO2 flux. However, the influence of the long-standing greater CO2 uptakes in the western Pacific than in the east and the dynamic change of this west-east difference remain unclear. In this paper, using the gridded surface ocean pCO2 product constructed by the stepwise FFNN algorithm, we reported an increasing west-east CO2 flux difference from 0.41 PgC yr-1 in 1992 to 0.73 PgC yr-1 in 2020. This increase was mainly attributed to the strengthening western Pacific carbon sink and relatively stable eastern Pacific carbon source. During El Nino events, the west-east CO2 flux difference decreased significantly in a few years, and it then rose back rapidly when El Nino events ended. In addition, the increasing west-east difference in CO2 uptakes during the last three decades did not lead to a higher acidification speed in the western surface temperate Pacific than the east. The greater CO2 absorbed in the west was mainly transported to the deeper waters and caused a more significant carbon inventory change at 200-600 m than the eastern Pacific.